Participating in social exclusion: A reflexive account of collaborative research and researcher identities in the field. Issue 2 (June 2022) - Newitt, Simon; Thomas, Nigel Patrick
This paper offers a critical reflexive perspective on a Participatory Action Research project with young people at a site of 'advanced urban marginality' (Wacquant, 2008 ). Its purpose is to explore the ways in which habitus based inequalities in the research field (Bourdieu, 1977 ) contributed to a parallel process of marginalisation and exclusion in the act of participating. More specifically, we examine how a particular professional academic research identity and taxonomy of participatory social research, animated by a benign intent, nonetheless exerted an ideological form of control over the enquiry, administering and recycling feelings of failure and marginalisation among participants - including the 'professional' researcher. To draw out the different ways this control took form, our analysis centres on a particular exchange within the group concerned with the distribution of a one-off financial stipend to participants. We endeavour to draw some conceptual insights in our exploration of this exchange, and in conclusion offer some ideas for a 'good enough' practice of action research undertaken in comparable socio-economic and psycho-cultural conditions.